Update on the current modalities used to screen high risk youth for prediabetes and/or type 2 diabetes mellitus - Preneet Cheema Brar (Korean Society of Pediatric Endocrinology, 2019)
The modalities currently employed to screen for type 2 diabetes mellitus (T2DM)/prediabetes are HbA1c, fasting plasma glucose (FPG), and 2-hour plasma glucose (PG) during an oral glucose tolerance test (OGTT). The purpose of this review is to highlight the positive qualities and pitfalls of these diagnostic modalities and reflect on the most reasonable and effective approach to screen high risk youth. Given its inherent preanalytical advantages, glycated hemoglobin (HbA1c) continues to be the preferred diagnostic modality used by pediatricians to screen high risk youth. However, when the three aforementioned tests are performed in youths of different races/ethnicities, discrepant results for T2DM/prediabetes are observed. The prevalence rates for T2DM vary from 0.53% in Chinese youth (including youth of all body mass indexes) to 18.3% in high-risk, overweight, obese Korean youth. Moreover, the FPG is abnormal (>100 less than <126 mg/dL) in 15% of Korean youth versus 8.7% of Chinese youth. The prevalence rates for prediabetes are 1.49% in Chinese youth versus 21% in Emirati youth (HbA1c, 5.7%-6.4%). The coefficient of agreement, k, between these screening tests for T2DM are fair, 0.45-0.5 across all youth. However, using HbA1c as a comparator, the agreement is weak with FPG (k=0.18 in German youth versus k=0.396 in Korean youth). The American Diabetes Association (ADA) Standards of Medical Care Guidelines define "high risk youth" who need to be tested for T2DM and/or prediabetes. OGTT and HbA1c do not always detect T2DM in similar individuals. HbA1c may not be an ideal test for screening Hispanic and African American youth. FPG and OGTT are suitable screening tests for youth of ethnic minorities and those with cystic fibrosis or hemoglobinopathies. Performing all three tests either together or sequentially may be the only way to encompass all youth who have aberrations in different aspects of glucose homeostasis.